Fathers' experiences of living with cancer: a phenomenological study. (22nd March 2016) - O'Neill, C.; McCaughan, E.; Semple, C.J.; Ryan, A.
Abstract : There is a paucity of knowledge about fathers' experiences of cancer. This study explored the experiences of fathers diagnosed and living with cancer while also having parental responsibility for children. A hermeneutic phenomenological approach guided the study. Data were generated through 22 in‐depth interviews with 10 fathers throughout Northern Ireland. The findings evidenced that fathers' identities are challenged and frequently re‐shaped by the cancer experience, in many cases leading to an improved lifestyle behaviour. Heightened engagement with their children can provide a protective effect from the illness. On the other hand a lack of involvement led to frustration and low mood. The findings also demonstrated that father/child relationships were adversely affected by the social complexities that exist in the variances and diversity of fathers parenting roles and status. This knowledge contributes to our understanding of the complex relationships of fathers in non‐traditional roles. It extends our understanding of how, when stereotyped gendered roles are ascribed to fathers it can impact on a fathers' ability to fulfil the traditional breadwinner's role. This is knowledge that will inform health care professionals and enable them to provide gendered‐sensitive care that takes account of the masculine psychological responses that can shape the cancer experience.